Evaluation of the geotechnical behaviour of a volcanic soil wall with additions of lime and cement against landslides - Davila, C. (2020)
The construction of earth walls can be a significant response to prevent the next landslides from reaching the road and avoid accidents. Therefore, a material of the same slope was used and reinforced with mixtures of lime and cement, with this same reinforced material a mechanically stabilized hypothetical earth wall (MSE) was developed. An analysis of the original slope was developed to check if there was a possible failure through its safety factor. Then, a hypothetical wall was developed with a floor reinforced with mixtures, in order to assess its overall safety factor and its maximum landslides. According to the results, in principle it was determined that the dosage M-3 / C-4-4 improves in a range of 30% to 37% the friction angle. In addition, it was found that a reinforced wall, that is to say with Lime and cement additions, presents a better behaviour. In its effect, its displacements are about 8 mm and have a global factor of 1.23.